THE IMPACT OF INVESTMENTS ON THE EFFICIENCY OF USING THE RESOURCE POTENTIAL OF AGRICULTURAL ENTERPRISES - Ivaniv, S.I. (The actual problems of regional economy development, 2021)
Ukraine's agriculture needs modernization at this stage of development. One of the steps that can bring the level of activity of domestic agricultural enterprises to foreign ones is investment from various sources. Agricultural enterprises of Ukraine have all the opportunities to attract in their activities and in the development of technical equipment - foreign investment, given the rich chernozem Ukrainian lands and current trends in the consumption of organic products. The study aims to study in detail the relationship between the use of resource potential by agricultural enterprises and investment. The purpose of the study is to study and analyze the impact of various forms of investment on the activities of agricultural enterprises and the efficiency of resource potential. The study used the following methodological framework: grouping method to determine the forms of investment in agricultural enterprises; graphical method to reflect the volume of imports of new and used agricultural machinery, as well as the dynamics of capital investment in agriculture; calculation method for determining the value of the average annual absolute increase in capital investment in agriculture; analytical method for determining the deterrents of investment activity in agriculture. The article analyzes the possible forms of investment and their impact on the structural components of resource potential. As a result of the study, it was determined that the greatest impact of investment activities has on the technical component of the resource potential of agricultural enterprises. The study identifies the main factors that create an unfavorable climate in attracting investment in agriculture. The article contains recommendations on how to increase the investment attractiveness of the agricultural sector at the state level and at the level of agricultural enterprises themselves, especially when it comes to attracting foreign investment. The dynamics of capital investment is demonstrated, where as a result, the reduction of investment in recent years is determined. The results obtained during the study can be used by agricultural enterprises in planning the use of their own investment fund and attract foreign investment.